INHIBITORY TEST ANTIMICROBIAL OF SEAWEED EXTRACT FROM Padina sp. AGAINST THE GROWTH OF Vibrio parahaemolyticus, Staphylococcus aureus, Escherichia coli AND Salmonella thypimirium - Joice P. M. Kolanus; Edward J. Dompeipen (Pattimura Proceeding, 2017)
The content of secondary metabolites of seaweed as an antibacterial, antiviral, antifungal and sitotastik have great potential as a source of cure various diseases. Padina sp is one of brown algae which is potential to be a natural antibacterial agent. This research aims to determine the inhibitory potency of Padina sp. extract on the growth of Vibrio parahaemolyticus, Staphylococcus aureus, Escherichia coli, and Salmonella thypimirium bacterial. The extraction Padina sp using methanol as the solvent while the treated samples dilution of 0, 5, 10 and 50. Then measuring the inhibition by paper disc methods. Result showed that the diameter methanol extract of seaweed Padina sp. against bacterial the growth inhibition of E. coli each 26.5 mm with the very strong barriers response and 17.5 mm were classified as strong; on the growth of Salmonella thypimirium bacteria by 19 mm with a response barriers that were moderate but not have inhibitory effect on the growth of Vibrio parahaemolyticus and Staphylococcus aureus bacterial.